2016
DOI: 10.1049/iet-gtd.2015.0757
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation framework for development of cost‐effective monitoring in distribution networks

Abstract: This paper presents a novel optimisation methodology, Optimal Placement of Monitors (OPM Power ), for optimal device/monitor placement in distribution networks. OPM Power is developed based on gradient search and Particle Swarm Optimisation (PSO). The proposed method integrates network topology into search process via spanning trees and uses the historical experience for search guidance. The method is particularly suited for optimal placement problems in power systems. The application is illustrated on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Direct meter measurement is critical because of its accuracy and high influence in network analysis results. In the literature, it has demonstrated that different meter placement could greatly impact on the network analysis performance and eventually the network operation [35]. Thus, it is important to allocate the meters optimally around the distribution networks, and the analysis of meter placement strategy is attracting more attention than ever.…”
Section: Optimal Meter Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct meter measurement is critical because of its accuracy and high influence in network analysis results. In the literature, it has demonstrated that different meter placement could greatly impact on the network analysis performance and eventually the network operation [35]. Thus, it is important to allocate the meters optimally around the distribution networks, and the analysis of meter placement strategy is attracting more attention than ever.…”
Section: Optimal Meter Placementmentioning
confidence: 99%
“…For state-of-the-art SE models, heuristic or suboptimal algorithms are used widely for optimal placement of measurement meters especially for the purpose of SE. In general in the design of an optimization framework, three aspects should be considered in order to efficiently and accurately search for the optimal (minimum or maximum) value [35]: (1) trade-off between exploitation and exploration;…”
Section: Optimal Meter Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…Their residual part (i.e., the combined effect between DA −′ and FA − ) together with current DB − caused by the DG connected at B6 results in peak | − | at B6. The proposed approach is further validated on a 96-bus section of a generic UK distribution network [19,20], which is likely to be exposed to unbalance phenomena if unbalance sources exist in the network.…”
Section: Propagation Of Negative-sequence Voltagementioning
confidence: 99%
“…The estimated results can be used for distribution network operation and control, e.g., voltage regulation, load compensator, congestion management, phase imbalance correction and reactive power compensation [21], etc. The performance of voltage unbalance at all buses can also be estimated using general SE through postprocessing the estimated three-phase voltages [22][23][24].…”
Section: Power Quality Sementioning
confidence: 99%